2006
DOI: 10.1038/sj.jcbfm.9600347
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological FMRI: Measuring Opioid Effects on the BOLD Response to Hypercapnia

Abstract: Opioid binding to the cerebral blood vessels may affect vascular responsiveness and hence confound interpretation of blood oxygen level-dependent (BOLD) responses, which are usually interpreted as neuronal in origin. Opioid binding varies in different brain regions. It is unclear whether opioids alter neurovascular coupling, or whether their effects are purely neuronal. This study used BOLD functional magnetic resonance imaging (FMRI) to investigate the effect of a lopioid agonist remifentanil, on cerebrovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 56 publications
2
49
0
Order By: Relevance
“…A growing body of evidence shows that many diseases and pathologies -including brain injuries -alter neurovascular coupling and change BOLD signal without necessarily affecting neuronal function Gsell et al, 2000;Krainik et al, 2005;Lindauer et al, 2010;Sakatani et al, 2003Sakatani et al, , 2007. In the same vein, we must also consider that patients with severe brain injuries are usually on several medications, which can also influence neurovascular coupling (Bruhn et al, 2001;Luchtmann et al, 2010;Pattinson et al, 2007;Reinhard et al, 2010). We can attribute changes in BOLD signal to changes in neural activity if and only if signalling and vascular reactivity are not altered; and we can compare between groups (e.g., patients and controls) only if these properties are the same in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence shows that many diseases and pathologies -including brain injuries -alter neurovascular coupling and change BOLD signal without necessarily affecting neuronal function Gsell et al, 2000;Krainik et al, 2005;Lindauer et al, 2010;Sakatani et al, 2003Sakatani et al, , 2007. In the same vein, we must also consider that patients with severe brain injuries are usually on several medications, which can also influence neurovascular coupling (Bruhn et al, 2001;Luchtmann et al, 2010;Pattinson et al, 2007;Reinhard et al, 2010). We can attribute changes in BOLD signal to changes in neural activity if and only if signalling and vascular reactivity are not altered; and we can compare between groups (e.g., patients and controls) only if these properties are the same in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,[11][12][13][14][15][16][17][18][19][20][21][22] Most experimental studies of hypercapnia increase pCO 2 through rebreathing techniques or 5% CO 2 air mixtures. These methods result in a mild increase in pCO 2 of approximately 5 to 8 mm Hg.…”
Section: Discussionmentioning
confidence: 99%
“…However, the opioid influence on the hypercapnic response was evaluated by Pattinson et al, 19 who found that opioids did not modulate the vascular reactivity with regard to blood oxygen level-dependent functional MR imaging signal intensity changes.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…One method of identifying the effects of pharmacologic agents on the properties of vasodilation is a breath holding task. Pattinson et al [52] employed a breath holding task to demonstrate that the hemodynamic response observed was not a global effect and was in fact localized to target regions and were related to neural activity.…”
Section: Remaining Issuesmentioning
confidence: 99%